Mesozoic–Cenozoic evolution of the Danba dome (Songpan Garzê, East Tibet) as inferred from LA-ICPMS U–Pb and fission-track data. (15th April 2015) - Jolivet, M.; Roger, F.; Xu, Z.Q.; Paquette, J.-L.; Cao, H.
Highlights: Zircon U–Pb ages confirm Neo-Proterozoic magmatic events in the Danba basement. Mesozoic magmatism occurred between about 230 Ma and 170 Ma in the Danba region. The Mesozoic ductile deformation in the Danba area occurred between 200 and 190 Ma. The Danba dome is a Late Miocene–Pliocene (10–4 Ma) tectonic structure. The growth of the Danba dome is linked to backthrust deformation of the Longmen Shan. Abstract: The eastern margin of the Tibetan Plateau is a key region to understand the formation and tectonic evolution of the plateau. Most studies concentrated on the Longmen Shan range that corresponds to the tectonically very active boundary between the Tibetan Plateau and the Sichuan Basin. This work addresses the deformation and exhumation pattern in the poorly understood metamorphic Danba dome situated at the conjunction between the southern Longmen Shan range and the major strike-slip Xian Shui He fault. The Early Mesozoic and Cenozoic evolution of the dome are then compared to the regional evolution of eastern Tibet. The about 830 Ma zircon U–Pb ages obtained on the Gezong and Gongcai gneiss as well as U–Pb ages on inherited zircons in the Early Mesozoic granites confirm the occurrence of Neo-Proterozoic magmatic episodes in the Danba basement at 800–900 Ma and 650–750 Ma. Following the closure of the Palaeotethys Ocean, granitoids were emplaced in the Danba metamorphic basement and Triassic cover from about 230 Ma to about 170 Ma. The western part of the Lian He Kau granitic massif, emplaced (between 210 and 200 Ma) within the Triassic cover sequence of the dome was only slightly affected by the Early Mesozoic deformation. However, in the eastern, deeper level compartment of the massif, ductile deformation occurred between 200 and 190 Ma, contemporaneous with the onset of the Barrovian-type metamorphism dated at 200–180 Ma. That deformation is compatible with the Early Mesozoic deformation observed in the Longmen Shan range and with the development of the large-scale décollement level in the Songpan Garzê area. Apatite fission track data then indicate that, following the Oligocene–Middle Eocene onset of eastward motion of the Songpan Garzê terrane, the Danba dome developed as a crustal-scale antiform during the Late Miocene–Early Pliocene (10–4 Ma). The exhumation was controlled by the Lian He Kau fault (a major transpressive structure parallel to the Xian Shui He fault) and the associated Manai thrust faults. Regionally, while the Oligocene–Middle Miocene exhumation phase seems to have been of regional extent, the Late Miocene to Present day phase is localised along the Longmen Shan range thrusts as well as along the back-thrusts formed by the Lian He Kau, Manai and associated faults.